Longitudinal growth faltering among young children in Burkina Faso - Cliffer, Ilana. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Food and Nutrition Policy and Programs.; Advisor: Beatrice Rogers.; Committee: William Masters, Elena Naumova, and Nandita Perumal.; Keywords: Health sciences, Nutrition, and Environmental health.